A chemical epigenetic tool to probe site-specific DNA-binding protein complexes - Jiajun Zhu; Zhucui Li; Dongxiang Xue; Zihe Meng; Sida Shao; Julian Pulecio; Guoan Zhang; Danwei Huangfu; Todd Evans; Shuibing Chen; Peter G. Schultz (Proceedings of the National Academy of Sciences, 2025)
Site-specific DNA binding by proteins is critical for regulating transcriptional activity and cell fate decision. However, identifying proteins bound to specific genomic regions (e.g., promoter or enhancer regions) remains challenging. To address this, we developed a chemical epigenetic tool, named Site-specific noncanonical amino acid-mediated capture of protein (SCOPE), incorporating a photo-crosslinking amino acid into a nuclease-deficient dCas9 mutant. Human pluripotent stem cells (hPSCs) carrying SCOPE enable the capture of proteins bound to, in theory, any genomic location, facilitating the study of the cell context–dependent DNA–protein interactions. Using SCOPE, we identified the OCT4/SOX2/CARHSP1 complex binding to the NANOG promoter to maintain pluripotency in hPSCs. During ectoderm differentiation, ZIC2 acts as a competitive inhibitor, binding the same promoter region to downregulate NANOG expression and promote differentiation. Additionally, SCOPE identified that ZNF8 binds to the distal regulatory region of OCT4 to maintain naïve pluripotency. In summary, SCOPE provides a robust system for uncovering cell context–dependent, site-specific genome regulators, offering valuable insights into gene regulation networks driving cell fate transitions.